A POTASSIUM-SELECTIVE SULFIDE-LINKED REDOX-ACTIVE FERROCENE IONOPHORE THAT EXHIBITS EXTRAORDINARY ELECTROCHEMICAL RECOGNITION BEHAVIOR - Beer, P; Danks, J; Hesek, D; Mcaleer, J (1993)
A new ferrocenyl ionophore L1 selectively complexes, electrochemically recognises and responds to, via an extraordinary cathodic perturbation of the metallocene redox centre, the potassium guest cation in the presence of equimolar amounts of sodium ions.